2004
DOI: 10.1038/sj.sc.3101636
|View full text |Cite
|
Sign up to set email alerts
|

Exploring quality of life following high spinal cord injury: a review and critique

Abstract: Study design: Review. Objectives: To explore the concept of quality of life (QOL), critique the practice and problems of assessing QOL following spinal cord injury (SCI) and to review the findings of studies into QOL for people with SCI both below and above the level of C4. Methods: Relevant articles were identified from the Medline and CINAHL databases for approximately the period 1990-2003, cross-indexing 'spinal cord injury' or 'quadriplegia/ tetraplegia' with 'quality of life', 'life satisfaction', 'social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
68
2
14

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 106 publications
8
68
2
14
Order By: Relevance
“…28 Anthropologists and disability researchers have demonstrated that Western conceptions of QOL reflect culturally specific and not universal values. 3 To enhance comparability, studies were therefore excluded if they had been undertaken outside the context of the 'Western' (minority) world. Articles were not included if their study sample was not exclusively spinal cord injured.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…28 Anthropologists and disability researchers have demonstrated that Western conceptions of QOL reflect culturally specific and not universal values. 3 To enhance comparability, studies were therefore excluded if they had been undertaken outside the context of the 'Western' (minority) world. Articles were not included if their study sample was not exclusively spinal cord injured.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] However, while the need to understand more about the perceptions and determinants of life's quality held by people with SCI is undisputed, there have been difficulties in studying a concept that lacks a clear definition and that is perceived differently by different people, in differing circumstances and at different times of their lives. 3,4 The vast majority of research into QOL following SCI has adopted a quantitative approach, 3 reflecting researchers' assumptions that quality can be measured quantitatively; that the determinants of QOL following SCI can be reliably predicted by able-bodied researchers; and that the subjective experience of a life can be objectively and accurately discerned by another person. These assumptions have been challenged [5][6][7][8][9][10] and it has been argued that the results of these studies are both misleading and of questionable value.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations